Evaluation of NAD(H) analogues as selective inhibitors for Trypanosoma cruzi S-Adenosylhomocysteine hydrolase - Li, Qing-Shan (2009)
S-Adenosylhomocysteine (AdoHcy) hydrolases (SAHHs) from human sources (Hs-SAHHs) bind the cofactor NAD(+) more tightly than several parasitic SAHHs by around 1000-fold. This property suggests the cofactor binding site of this essential enzyme as a potential anti-parasitic drug target, e.g., against SAHH from Trypansoma cruzi (Tc-SAHH). The on-rate and off-rate constants and the equilibrium dissociation constants were determined for NAD(+)/NADH analogues and suggested that NADH analogues were the most promising for selective inhibition of Tc-SAHH. None significantly inhibited Hs-SAHH while S-NADH and H-NADH (Fig. 1) reduced the catalytic activity of Tc-SAHH to <10% in six minutes of exposure.